THE EFFECT OF PAPAIN ENZYMES ADDITION IN FEED ONGROWTH AND SURVIVAL RATE OF CACHAMA(Colossoma macropomum) IN THE RECIRCULATION SYSTEM - Monika Sari Br Sembiring; Mulyadi Mulyadi; Iskandar Putra (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT                              This research was conducted on May 1 - June 10, 2019, at the Laboratory of Aquaculture Technology, Faculty of Fisheries and Marine, University of Riau. This study aims to determine the best dosage of Papain enzymes mixed in commercial feed to see the growth and survival of Cachama(Colossoma macropomum). The research container used was a 60x40x40 cm3 aquarium with 12 aquariums with a stocking density of 25 fish/aquarium. This study used a Completely Randomized Design with one factor of four levels of treatment and three replications. Each treatment was given the addition of papain enzymes as much as P0 (without the papain enzyme ), P1 (1,25% / kg), P2 (2,25%/ kg) and P3 (3,25%/ kg) of feed. The results showed that the best treatment found in P2 (2,25% / kg) of feed resulted in absolute weight growth of 11,95 g, growth of the absolute length of 4,96 cm, a specific growth rate of 6,86%, food convertion ratio of 0,93 and livelihood 100 %. Keywords: Papain Enzyme, Growth, Colossoma macropomum